Fabrication of nanomedicines for precisely controlled combination therapy - Santos, Hélder A. (Henry Stewart Talks, 2015)
Nanotechnology and nanomaterials, Drug delivery and drug delivery systems (DDS), Porous silicon (PSi) biomaterial, Microfluidics in biomedical applications